RELATIONSHIPS BETWEEN GENERAL HEALTH CONCERN AND ILLNESS UNCERTAINTY IN DIABETICS: ROLE OF SELF-REGULATION - Afzal, Aafaque; Atta, Mohsin; Malik, Najma Iqbal (Journal of Postgraduate Medical Institute, 2021)
Objective: To investigate the relationship between general health concern and illness uncertainty in diabetics and to find out the role of self-regulation. Methodology: This cross-sectional study was conducted in the department of Psychology, University of Sargodha from April to September 2018. A sample of 250 diabetic patients was enrolled inclusive of males and females from different hospitals of Sargodha, Joharabad and Khushab. Measure of Health Status Form (SF-36), Illness Uncertainty Scale and Self-Regulation Questionnaire (SRQ) were administered. Data was analyzed with the help of SPSS version 24. Results: Results of the present study indicated a significant negative relationship between general health concern and illness uncertainty (Î² = -.34, p < .001). Low level of self-regulation was also negatively correlated with illness uncertainty in diabetics (Î² = -1.76, p < .05). Moreover, self-regulation played a significant moderating role between the relationship of general health concern and illness uncertainty (Î² = .30, p < .001). Conclusion: Illness uncertainty significantly and negatively affected the general health concern and self-regulation of diabetics. Moreover, self-regulation of diabetics was also vital as a moderator between the relationship of general health concern and illness uncertainty.